Community Health Volunteers in Primary Healthcare in Rural Uganda: Factors Influencing Performance - Kuule, Yusufu; Dobson, Andrew Eric; Woldeyohannes, Desalegn; Zolfo, Maria; Najjemba, Robinah; Edwin, Birungi Mutahunga R.; Haven, Nahabwe; Verdonck, Kristien; Owiti, Philip; Wilkinson, Ewan (Frontiers in Public Health, 2017)
Introduction Community health volunteers (CHVs) play an integral role in primary healthcare. Several countries rely on CHV programs as a major element in improving access to care and attaining universal health coverage. However, their performance has been heterogeneous and at times context-specific, and influenced by multiple factors. We describe the socio-demographic and workplace characteristics affecting CHVs’ performance in a public health program in rural western Uganda. Methods This was a cross-sectional study based on routine program data of CHVs serving the catchment of Bwindi Community Hospital, Kanungu District, South Western Uganda, in 2014 and 2015. Information was collected on individual socio-demographic and workplace characteristics of the CHVs. To assess their work output, we defined study-specific targets in terms of attendance at monthly CHVs’ meetings with community health nurses, households followed-up and reported, children screened for malnutrition, immunization coverage, and health facility deliveries. Frequencies and proportions are reported for characteristics and outputs and odds ratios for study-specific factors associated with overall performance. Results Of the 508 CHVs, 65% were women, 48% were aged 35 years and below, and 37% took care of more than the recommended 20–30 households. Seventy-eight percent of the CHVs had ≥80% of pregnant women under their care delivering in health units, 71% had ≥95% of the children on schedule for routine immunization, while 27% screened ≥75% of the children under 5 years for malnutrition. More refresher trainings was associated with better overall performance [adjusted odds ratio (aOR): 12.2, 95% confidence interval (CI): 1.6–93.6, P = 0.02] while overseeing more than the recommended 20–30 households reduced overall performance (aOR: 0.6, 95% CI: 0.4–0.9, P = 0.02). Conclusion Being in-charge of more than the recommended households was associated with reduced performance of CHVs, while more refresher trainings were associated with improved performance. If the CHVs are to remain a strategic pillar in universal health coverage, it is imperative to address those factors known to impact on their performance.